Germany's New "Security Architecture"? Long-Term Unemployed and Rent-a-Cops - Eick, Volker (Social justice, 2011)
The article looks at the institutions of security and policing in Germany, as of 2011. The author describes the expansion of what is referred to in government policy statements as the country's "security architecture" to include traditional public-sector police forces as well as private for-profit security companies and unemployed workers engaged in neighborhood watch and other security efforts through workfare programs. He discusses issues raised by the growth of private security firms and workfare parapolice, including their legal status in relation to the policing power of the state, the role of the nonprofit agencies administering the workfare programs, and the relationship of such security personnel to the residents of the low-income areas where they are often assigned.